The SAGE handbook of the history, philosophy and sociology of international relations - Gofas, Andreas; Hamati-Ataya, Inanna; Onuf, Nicholas Greenwood (2018)
This Sage handbook offers a panoramic view of the broad field of international relations by integrating three distinct but interrelated foci. It retraces international relations' historical devolopment as a professional field of study, expolores the philosophical foundations of international relations, and interrogates the sociological mechanisms through which scholarship is produced and the field is structured. The 41 chapters are structured into five parts: 01. Reflections on a disciplinary practice02. Imagining the international, acknowledging the global03. The search for (an) identity04. International relations as a profession05. Looking ahead: the future of meta-analysis.
Includes bibliographical references and index.
Keywords: International relations